Portuguese estuarine systems and their essential ecological role for some fish species: trends and predictions in face of global changes - Brandão, Pedro Reis (2022)
Tese de mestrado, Ecologia Marinha, Universidade de Lisboa, Faculdade de Ciências, 2022